A brachiopod biotope associated with rocky bottoms at the shelf break in the central Mediterranean Sea: Geobiological traits and conservation aspects. Issue 2 (6th January 2020) - Angeletti, Lorenzo; Canese, Simonepietro; Cardone, Frine; Castellan, Giorgio; Foglini, Federica; Taviani, Marco
Abstract: In the Recent, brachiopods only seldom occur in benthic communities. A biotope dominated by Megerlia truncata was identified in 2013 by exploration of the south‐easternmost Adriatic margin by Remotely Operated Vehicle (ROV). Emerging rocky substrates next to the shelf break at approximately 120 m appear intensively exploited by this eurybathic rhynchonelliformean brachiopod, attaining a population of more than 300 individuals per m 2 . Calcareous red algae are almost ubiquitous at this site and preferentially encrust sectors of the substrate where brachiopods are minimal. This Megerlia biotope is a novel finding for this part of the Mediterranean Sea, similar to a situation previously observed in the Western Basin, off the Mediterranean French coast. It is proposed that this remarkable brachiopod biotope and the adjacent rhodolith bed are considered important for conservation management.